Late Miocene-early Pliocene stable isotope record of benthic foraminifera from ODP Site 177-1088 in the sub-Antarctic South Atlantic - Billups, Katharina (Supplement to: Billups, K (2002): Late Miocene through early Pliocene deep water circulation and climate change viewed from the sub-Antarctic South Atlantic. Palaeogeography, Palaeoclimatology, Palaeoecology, 185(3-4), 287-307, https://doi.org/10.1016/S0031-0182(02)00340-1, 2002)
Benthic foraminiferal stable isotope records for the past 11 Myr from a recently drilled site in the sub-Antarctic South Atlantic (Site 1088, Ocean Drilling Program Leg 177, 41°S, 15°E, 2082 m water depth) provide, for the first time, a continuous long-term perspective on deep water distribution patterns and Southern Ocean climate change from the late Miocene through the early Pliocene. I have compiled published late Miocene through Pliocene stable isotope records to place the new South Atlantic record in a global framework. Carbon isotope gradients between the North Atlantic, South Atlantic, and Pacific indicate that a nutrient-depleted watermass, probably of North Atlantic origin, reached the sub-Antarctic South Atlantic after 6.6 Ma. By 6.0 Ma the relative proportion of the northern-provenance watermass was similar to today and by the early Pliocene it had increased to greater than the modern proportion suggesting that thermohaline overturn in the Atlantic was relatively strong prior to the early Pliocene interval of inferred climatic warmth. Site 1088 oxygen isotope values display a two-step increase between ~7.4 Ma and 6.9 Ma, a trend that parallels a published delta18O record of a site on the Atlantic coast of Morocco. This is perhaps best explained by a gradual cooling of watermasses that were sinking in the Southern Ocean. I speculate that relatively strong thermohaline overturn at rates comparable to the present day interglacial interval during the latest Miocene may have provided the initial conditions for early Pliocene climatic warmth. The impact of an emerging Central American Seaway on Atlantic-Pacific Ocean upper water exchange may have been felt in the North Atlantic beginning in the latest Miocene between 6.6 and 6.0 Ma, which would be ~1.5 Myr earlier than previously thought.